Distribusi semen ionomer kaca pada gigi permanen di Puskesmas karang pule : (Studi pada kota mataram NTB tahun 2016-2020) - Rofilah Sandaeng, Siti; Amaludin Gunawan, Juanita; Ariwibowo, Taufiq (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Health is the most important factor in human survival. Dental and oral health is part of overall health. Caries is a disease most commonly found in the oral cavity so that is the main problem of oral health. Dental caries should be taken care of by filling. Nowadays have been found filling materials for caries for example glass ionomer cement (GIC). At Karang Pule Health Center located in Mataram City, GIC is the preferred material often chosen by dentists for caries. Objective: To know about the use of GIC as restoration material in Karang Pule Health Center located in Mataram, NTB in 2016-2020. Method: This research is a descriptive retrospective research using the cross sectional approach by taking the medical records of patients in Karang Pule Health Center whom were given GIC as the filling material. Result: There were 628 patients using GIC and categorized based on the year of fillng, age,sex, region of feeling and the period of teeth in each patient. Conclusion: Based on the year of filled, it shows that 2017 was the highest frequency of fillings with GIC, which was 193 patients (30.7%), while in 2020 it was the least frequency, which was 17 patients (2.7%). GIC is most widely used in patients aged 26-35 years (adults), as many as 202 patients (32.2%) and the least is done in patients aged 56-65 years and over. GIC treatment is more often accepted by female patients than male patients. The mandibular posterior region of the teeth is the region most filled by GIC.